Formulasi dan Identifikasi Senyawa Minyak Atsiri Citrus hystrix DC. dengan GC-MS untuk Aktivitas Repelan terhadap Nyamuk Aedes aegypti - Juliadi, Debby; Cahyaningsih, Erna; Suena, Ni Made Dharma Shantini (Jurnal Ilmiah Medicamento, 2025)
Plant-based mosquito control offers a promising alternative to reduce the health and environmental risks associated with chemical insecticides. Citrus hystrix DC. (kaffir lime), a member of the Citrus genus, produces essential oils rich in bioactive compounds such as limonene, citronellal, and terpinolene, which are known for antimicrobial and insecticidal properties. This study focused on extracting essential oil from kaffir lime fruit, identifying its chemical constituents using gas chromatography–mass spectrometry (GC-MS), and evaluating the repellent efficacy of its spray formulation against Aedes aegypti. Essential oil was obtained through steam distillation and analyzed by GC-MS to determine its chemical profile. Repellent activity was assessed experimentally using 100 adult mosquitoes divided into five treatment groups, with spray formulations prepared at concentrations of 5%, 10%, and 15%. Data was analyzed using one-way ANOVA followed by post-hoc tests. GC-MS analysis revealed 90 compounds, with five major constituents: D-limonene (14.57%), limonene (13.92%), citronellal (6.66%), terpinolene (6.47%), and α-terpineol (5.74%). Repellent testing demonstrated that the 15% concentration provided the highest protection against mosquito landings. These findings confirm the potential of kaffir lime essential oil as an effective natural mosquito repellent and provide a scientific basis for developing eco-friendly, plant-derived vector control products. This research contributes to reducing dependence on synthetic insecticides and supports sustainable strategies for vector management that prioritize human health and environmental safety.